Wujud-Based Character Education: Actualisation of The Prophet's Educational Character as Uswatun Hasanah - Hasib Arista; Baihaqi Baihaqi; Ahmad Musadad; Ainun Syarifah; Tri Pujiati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This research is motivated by the phenomenon of increasing cases of juvenile delinquency, moral and ethical decline, and various forms of social deviance that still occur among those who have received education. This study aims to identify and evaluate character education methods based on the actualisation of the exemplary values of the Prophet Muhammad as Uswatun Hasanah. The research method used is qualitative, with a descriptive approach, combining literature from various sources, such as journals, books, and holy books, with authentic evidence from the community. The results showed that implementing character education grounded in the values of the Prophet Muhammad changed individual behaviour towards greater moral conduct, as the Prophet succeeded in transforming jahiliyah society into one full of politeness. The conclusion of this study is that character education grounded in the example of the Prophet Muhammad is effective in shaping individuals with faith, devotion, and noble character. Suggestions for further research include deepening the implementation of these values in the modern education system and conducting comparative studies with existing character education approaches.